Responses of zooplankton to long-term environmental changes in a small boreal lake - Lehtovaara, Anja; Arvola, Lauri; Keskitalo, Jorma; Olin, Mikko; Rask, Martti; Salonen, Kalevi; Sarvala, Jouko; Tulonen, Tiina; Vuorenmaa, Jussi
2015